The Effect of Mobile Learning In The Acquisition of Nursing Skills - Bilgiç, Şebnem; Çelikkalp, Ülfiye; Temel, Münire (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: The use of mobile technologies is very widespread among the younger population. This study was conducted to determine the effect of education with mobile support on the skill levels of a sample of nursing students in Tekirdağ/Turkey. Methods: This quasi-experimental study was conducted with 62 undergraduate students (31 experiments and 31 controls). The research was conducted with students attending the Spring semester of the first year and taking the nursing course fundamentals. First of all, subcutaneous injection skills were explained to the students, and training was given to them (the first part of education). A week later, the students’ skills were tested (pre-test), and then the students were divided into the two groups, balanced in terms of their gender and skill scores. A video about subcutaneous injection skills was prepared by the authors for the students in the intervention group, and students were allowed to access this video on their smartphones (Mobile). Three weeks after the first part of education, the students’ skill development was re-evaluated with the Subcutaneous (SC) Injection Skill Evaluation Checklist. Results: The mean age of the students who participated in the study was 19.04±1.16 years. The intervention group students watched the educational video with their smartphones 3.87 times on average. The difference between the post-test and pre-test scores of the subcutaneous injection skill was significant in the intervention group (7.71±4.55), compared with the controls (3.51±3.52). Thus, Nursing students in the intervention group, got a higher clinical skill for subcutaneous injection (P<0.001). Conclusions: Our results showed that a planned educational video through mobile learning could contribute to the clinical skill development of nursing students in the first year of education. It can inspire the university teachers to apply this method for clinical education of nursing students in other education areas.